The prospect of developing a data driven approach in the Russian economy - P. D. Krotov (Вестник университета)
The purpose of the study is to identify the potential for implementing the data driven approach in the economic environment in Russia, as well as to identify the key barriers and form methodological and practical recommendations for implementing the approach in organizations. The research methodology is based on general scientific methods application, such as theoretical and comparative analysis, systematization, and synthesis. It has been concluded that for full-fledged implementation of data driven approach it is necessary to carry out a sufficiently large number of changes in the direction of digitalization. The analysis of population and business digitalization has shown that, despite the high rate of use of digital services among them, the level of data driven technologies implementation in organizations remains low. The key obstacles to the transition to a data-driven approach and ways to overcome them have been identified. It has been revealed that the process of implementing the approach in organizations of different industries faces a number of limitations, but the basic principles remain unchanged, as well as the fact that the approach implementation can significantly improve organization’s efficiency. The authors formulate an idea of current options, opportunities, and advantages of integrating data driven methodology in Russian organizations.